MICROBUS STOP OPTIMIZATION BASED ON GIS FOR BUS FEEDER ON THE GUNUNG ANYAR – KENJERAN ROUTE - Firmansyah Maulana Azhali; Hera Widyastuti (Journal of Civil Engineering, 2023)
The Surabaya City Government seeks to provide adequate public transportation such as the Bus. The current condition on the Gunung Anyar - Kenjeran route is that there is no intermodal connectivity, so it is hoped that adequate intermodal connectivity will increase the demand for buses operating on the Gunung Anyar - Kenjeran route. For this reason, this research was conducted to plan the Microbus Stop as a stop location if the Microbus is to be used as a feeder for the Bus and determine the range of Microbus Stop services to meet the needs of the community. One of the locations chosen for this research is the Gunung Anyar - Kenjeran route, this is because this route is the route with the lowest number. Activities carried out to complete this research include conducting surveys of people who are active on and through the gunung anyar - kenjeran route, planning the alternative Microbus Stop location based on demand and infrastructure data and analyzing service coverage using the service area method. From the results obtained, it was found thatd majority of community made the move from Rungkut Sub-District to Gubeng Sub-District and Genteng Sub-District to Wonorejo Sub-District. Alternative Microbus Stop locations is divided into 2 schemes, namely demand-based and infrastructure-based. The demand-based Microbus Stop Scheme has 97 stop points while the infrastructure-based Microbus Stop scheme has 1270 stop points. Based on the results of the analysis of the service coverage of Microbus Stop, it shows that the infrastructure-based scheme has a better service area that meets community expectations, namely 5299.99 ha compared to the demand-based scheme which is only 1873.73 ha. The thing that causes the demand-based scheme to have a small service coverage area is due to the lack of demand data in Bulak District.